Growth, history, or institutions? What explains state fragility in sub-Saharan Africa - Graziella Bertocchi; Andrea Guerzoni (Institute for the Study of Labor (IZA), 2010)
We explore the determinants of state fragility in sub-Saharan Africa. Controlling for a wide range of economic, demographic, geographic and istitutional regressors, we find that institutions, and in particular the civil liberties index and the number of revolutions, are the main determinants of fragility, even taking into account their potential endogeneity. Economic factors such as income growth and investment display a non robust impact after controlling for omitted variables and reverse causality. Colonial variables reflecting the history of the region display a marginal impact on fragility once institutions are accounted for.
Keywords: O43; H11; N17; 330; State fragility; Africa; institutions; colonial history; Politische Stabilität; Institutionalismus; Kolonialismus; Wirtschaftswachstum; Afrika südlich der Sahara